Imaging Lenticular Autofluorescence in Older Subjects - Charng, Jason; Tan, Rose; Luu, Chi D.; Sadigh, Sam; Stambolian, Dwight; Guymer, Robyn H.; Jacobson, Samuel G.; Cideciyan, Artur V. (Investigative ophthalmology & visual science, 2017)
To evaluate whether a practical method of imaging lenticular autofluorescence (AF) can provide an individualized measure correlated with age-related lens yellowing in older subjects undergoing tests involving shorter wavelength lights. Lenticular AF was imaged with 488-nm excitation using a confocal scanning laser ophthalmoscope (cSLO) routinely used for retinal AF imaging. There were 75 older subjects (ages 47-87) at two sites; a small cohort of younger subjects served as controls. At one site, the cSLO was equipped with an internal reference to allow quantitative AF measurements; at the other site, reduced-illuminance AF imaging (RAFI) was used. In a subset of subjects, lens density index was independently estimated from dark-adapted spectral sensitivities performed psychophysically. Lenticular AF intensity was significantly higher in the older eyes than the younger cohort when measured with the internal reference (59.2 ± 15.4 vs. 134.4 ± 31.7 gray levels; P < 0.05) as well as when recorded with RAFI without the internal reference (10.9 ± 1.5 vs. 26.1 ± 5.7 gray levels; P < 0.05). Lenticular AF was positively correlated with age; however, there could also be large differences between individuals of similar age. Lenticular AF intensity correlated well with lens density indices estimated from psychophysical measures. Lenticular AF measured with a retinal cSLO can provide a practical and individualized measure of lens yellowing, and may be a good candidate to distinguish between preretinal and retinal deficits involving short-wavelength lights in older eyes.